Case Report on Fibrocalculous Pancreatic Diabetes in a Tertiary Hospital in Cumilla, Bangladesh (Central Medical College Journal, 2024)
Background: This case highlights the emergence of diabetes as a significant global health concern and discusses Fibrocalculous Pancreatic Diabetes, a distinct condition characterized by pancreatic calcification and chronic inflammation resulting in pancreatic dysfunction. While typically seen in young males in tropical regions with malnutrition, this case presents a rare instance of late-onset disease in a female, a reported case in Bangladesh. The case involves a 53-year-old non-alcoholic healthy female with a history of chronic pancreatitis leading to severe Insulin Dependent Diabetes Mellitus. Abdominal imaging revealed typical pancreatic calcifications consistent with Fibrocalculous pancreatic diabetes. This report underscores the importance of maintaining a high index of suspicion for atypical presentations, even when diagnostic criteria suggest childhood onset of the disease.Central Medical College Journal Vol 7 No 2 July 2023 Page: 116-120